(Retail) platform legitimation through municipal partnerships? - Sina Hardaker; Alexandra Appel (Digital Geography and Society)
Collaborations between digital platforms and governments are increasingly common, and understanding these partnerships is essential for grasping how platforms navigate and influence urban governance and market boundaries. This paper examines the legitimation processes involved in such collaborations, focusing on the eBay Deine Stadt initiative as a case study. This initiative, led by eBay, helps municipalities launch local online marketplaces, facilitating the digital transition for struggling brick-and-mortar retailers. Drawing on qualitative expert interviews with municipal stakeholders and a quantitative survey of retailers listed on the eBay Deine Stadt platform, this study offers several key contributions: Overall, it reveals the mixed outcomes of the eBay Deine Stadt initiative, adding to the discussion on platform legitimation in response to traditional retail decline. The study demonstrates the role of municipalities and government institutions in shaping the narrative of platforms as urban problem-solvers and highlights the absence of strategic planning by municipalities in their collaborations with digital platforms, noting that some urban actors promote a positive local perception, thereby potentially legitimizing increasing platformization. The study identifies institutional work as central to this legitimation process, highlighting a clear shift towards general validation.